Ceremony and ritual in Japan : religious practices in an industrialized society - Bremen, Jan van, 1946-2005; Martinez, D. P. (Dolores P.), 1957- (Nissan Institute/Routledge Japanese studies series., 1995)
Japan is one of the most urbanised and industrialised countries in the world. Yet the Japanese continue to practise a variety of religious rituals and ceremonies despite the high-tech, highly regimented nature of Japanese society. Ceremony and Ritual in Japan focuses on the traditional and religious aspects of Japanese society from an anthropological perspective, presenting new material and making cross-cultural comparisons. The chapters in this collection cover topics as diverse as funerals and mourning, sweeping, women's roles in ritual, the division of ceremonial foods into bitter and sweet,